Prevalence of refractive errors among primary school children (7-14 years) in Motherwell Township, Eastern Cape, South Africa - Akuta, Godwin Chukwuemeka (University of Limpopo, 2015)
Background: Uncorrected refractive errors remain a public health problem among different population and age groups worldwide, including South Africa. Refractive error has serious visual and functional impacts on those affected. In children, refractive errors may negatively affect the academic pursuits and activities of daily living such as reading. Aims and Objectives: To determine and document the prevalence, types and magnitude together with age and gender differences of refractive errors among primary school children in Motherwell Township, Eastern Cape Province, South Africa. Methods: This was a quantitative, cross sectional refractive error study. Four hundred and twenty one (421) school children aged 7 – 14 years were randomly selected from five randomly selected schools in Motherwell Township, Eastern Cape Province, South Africa. Visual examination which included unaided and aided visual acuity (with LogMAR E chart), non-cycloplegic autorefraction, subjective refraction, internal and external examination of the eye using an ophthalmoscope was conducted. Refractive errors were measured with an autorefractor, refined subjectively and findings presented in spherical form. Hyperopia was defined as a spherical equivalent (SE) of +0.50 D or greater, myopia as spherical equivalent of -0.50 D or greater. A cylindrical power of -0.50 DC (D cylinder) or greater was considered as astigmatism. Results: The prevalence of hyperopia, myopia and astigmatism among the children were 25.2%, 18.7% and 58.0% respectively. Hyperopia ranged from +0.50 to +3.62 D and myopia ranged from -0.50 D to -20.25 D in the right eyes with a mean of -0.17 ± 1.7 D. In the left eye, hyperopia ranged from +0.50 to +2.62 D and myopia ranged from -0.50 to -20.62 D with a mean of -0.12 ± 1.7 D. Astigmatism in the right eyes ranged from -0.50 to -5.50 D with a mean of -0.6 ± 0.52 D and in the left eye ranged from -0.50 to -4.00 D with a mean of -0.6 ± 0.45 D respectively. Association between hyperopia and age was not statistically significant (p = 0.839), also refractive error and gender was statistically insignificant (p = 0.120). Against-the-rule (ATRA) astigmatism (43.4%) was more common, followed by with-the-rule (WTRA) astigmatism (39.0%) and oblique, (all other meridians) (17.6%). There was a significant association between types of astigmatism and age (p = 0.05), more so inter-gender difference in the prevalence of different types of astigmatism was not statistically significant (p = 0.774). Conclusion: The study concludes that refractive error has high prevalence of 43.9% in this children population. Astigmatism (58.0%) was more common followed by hyperopia (25.2%) v and myopia (18.7%). Although hyperopia was not age dependent, there was obvious relationship pattern between female genders and hyperopia in the present study. Population-based vision screening or at least school visual screening in the rural communities of Motherwell Township is, therefore recommended. Vision screening and proper eye examination with appropriate optical compensation will improve the activity of daily living and quality of life of those affected. Key words: Refractive error, hyperopia, myopia, astigmatism, school children
Thesis (MPH.) --University of Limpopo, 2015
Keywords: Refractive error; Hyperopia; Myopia; Astigmatism; School children; Astigmatism; Astigmatism.; Hyperopia